Impact of Intramural and Extramural Vascular Invasion on Stage II-III Colon Cancer Outcomes - Leijssen, Lieve G.J. (J Surg Oncol, 2019)
BACKGROUND AND OBJECTIVES: Vascular invasion, in particular extramural venous invasion (EMVI), is a pathologic characteristic that has been extensively studied in rectal cancer but rarely in colon cancer. This study aims to evaluate its prognostic role in stage II-III colon cancer. METHODS: All stage II-III colon cancer patients who underwent surgery between 2004–2015 were reviewed. We divided the study group into patients without invasion, with intramural invasion only (IMVI), EMVI only, and both IMVI/EMVI (n=923). RESULTS: EMVI was associated with other high-risk features, including T4, N+ disease, lymphatic, and perineural invasion (P<0.001). EMVI+ patients had considerably higher rates of locoregional and distant recurrence and subsequently disease-specific mortality (stage-II: odds ratio (OR) 3.64, P=0.001, stage-III OR:1.94, P=0.009), whereas outcomes were comparable between IMVI and no vascular invasion (OR:1.21, P=0.764, OR:1.28, P=0.607, respectively). The adjusted hazard ratios for EMVI+ patients on disease-free survival, and disease-specific survival were 2.07 (P<0.001), 1.67 (P=0.027), respectively. Moreover, EMVI+ stage-II patients fared worse than EMVI– stage-III patients, even after adjusting for adjuvant chemotherapy. CONCLUSION: EMVI is a strong predictor for worse oncologic outcomes in stage II-III colon cancer patients, whereas IMVI is not. It is also associated with worse outcomes compared in patients with higher stage disease who are EMVI negative.